Optimal Seismic Intensity Measure Selection for Isolated Bridges under Pulse-Like Ground Motions - Linwei Jiang; Jian Zhong; Min He; Wancheng Yuan (Advances in Civil Engineering)
Isolated bridges are commonly designed in the near-fault region to balance excessive displacement and seismic force. Optimal intensity measures (IMs) of probabilistic seismic demand models for isolated bridges subjected to pulse-like ground motions are identified in this study. Four typical isolated girder bridge types with varied pier height (from 4 m to 20 m) are employed to conduct the nonlinear time history analysis. Totally seven structure-independent IMs are considered and compared. Critical engineering demand parameters (EDPs), namely, pier ductility demands and bearing deformation along the longitudinal and transverse directions, are recorded during the process. In general, PGV tends to be the optimal IM for isolated bridges under pulse-like ground motions based on practicality, efficiency, proficiency, and sufficiency criterions. The results can offer effective guidance for the optimal intensity measure selection of the probabilistic seismic demand models (PSDMs) of isolated bridges under pulse-like ground motions.